Eye tracking and child sexual offenders: a systematic review - Tony Godet; Gérard Niveau (Oxford University Press, 2021)
Eye tracking is used in sexology to identify attractiveness and sexual desire indirectly. This systematic review summarizes results of works that have used eye tracking to analyse paedophilic interest in order to investigate its potential as a useful forensic tool. Six studies met the inclusion criteria. Five of them concerned a large study project and used approximatively the same sample of paedophiles (inpatients), forensic patients (without a sexual interest in children) and healthy controls to make comparisons between the three groups. One study added 11 self-declared paedophiles (outpatients) for a comparison between inpatient paedophiles, outpatient paedophiles and controls (healthy and forensic inpatients). One study compared a group of child sexual offenders with non-offenders. All studies used static pictures of male and female subjects at different pubertal stages. Some studies divided every picture into a different area of interest. Dependent variables used are fixation latency (early attention) and relative fixation time, (later attention). Each study identified significant differences between the paedophile group versus other groups: shorter fixation latency on child pictures, longer fixation time on child pictures and number of fixation most important on child pictures. Two scores (age preference index and attentional control index) showed hight and/or moderate sensitivity and specificity. Although the results suggest the eye tracking can discriminate between paedophile interest and non-paedophile interest, there are too few studies on this specific topic and further research is needed with larger and different sample, carried out by different research teams. If these findings were confirmed, it remains unclear as to their impact in a forensic context when presented openly in Court.